Back Cover Image, Volume 39, Number 2, February 2020. Issue 2 (10th February 2020) - Yamanishi, Tomonori; Kaga, Kanya; Sakata, Koichi; Yokoyama, Teruhiko; Kageyama, Shinji; Fuse, Miki; Tokunaga, Shoji
Abstract : The Back Cover : The cover image is based on the ORIGINAL CLINICAL ARTICLE A randomized controlled study of the efficacy of tadalafil monotherapy versus combination of tadalafil and mirabegron for the treatment of persistent overactive bladder symptoms in men presenting with lower urinary tract symptoms (CONTACT Study) by Tomonori Yamanishi et al., https://doi.org/10.1002/nau.24285 . Cover Credit : Cover image © Tomonori Yamanishi Images